Red Square - the Myth and the Reality - Oliver, Bobbie (2005)
The Government Railway Workshops at Midland had few lengthy industrial disputes during its 90 years of existence, yet despite this apparently calm exterior, it was a highly contested site, divided not only into 'blue' and 'white-collar' territories or 'works' and 'management' but within those broad demarcations into the territory of particular trades, between whom a lively rivalry flourished. Yet of all these places, the two that most excite the memory of past employees and catch the imagination of visitors to the site a decade after the closure of the Workshops are the flagpole and 'Red Square'. This paper discusses the various roles of 'Red Square' as a site for the propagation and spreading of political ideas, a symbol of workers' defiance against the Workshops 'hierarchy' and a site for myth making. It concludes with a consideration of how areas such as 'Red Square' might be interpreted and maintained in any significant way in the process of re-developing the site.